ЯМБІЧНІ РИТМИ В ПОЕЗІЇ УКРАЇНСЬКИХ І РУМУНСЬКИХ СТАРШИХ СИМВОЛІСТІВ - Paladian, Kristiniia (ПП Цюпак А.А., 2017)
The article is devoted to the comparative and typological analysis of meter and rhythm of Ukrainian and Romanian early symbolists. Such investigation of metric repertoire will give the possibility of stating the relationship of classical and non-classical versification at the beginning of the 20th century and find out how the theoretical basis of European level was realized. It is shown that in both literatures classical versification dominates. In the works of early symbolists the range of traditional metric and rhythmic forms created by the poetry of previous period is actively used. Among them both in Romanian and Ukrainian literature iambic meters prevail; moreover in Romanian poetry their number is considerably higher. Iambic forms in both literatures are built on the law of regressive accent dissimilation, while strongly accentuated and weakly accentuated feet alternate in the poem through one from the end to the beginning. But in Romanian poetry the tendency to leveling of rhythmic curve at the expense of stronger accent of the first foot is felt. The most often used method in both literatures becomes iambic tetrameter with the traditional type of rhythm. Iambic hexameter in each literature is different: in Romanian hexameter there is caesura accumulation of one syllable, which creates symmetrical type of rhythm; Ukrainian hexameter is inherent of asymmetrical rhythm. The characteristic feature of Romanian versification is the experiments in the segment of the shortest monometric or the longest octametric lines. Most often the poets experimented in the realm of different-length iambic structures, in which the transference from one type of rhythm to another is observed.
Iambic rhythm in the poetry of Ukrainian and Romanian early symbolists
Keywords: symbolism; syllabo-tonic versification; ictus; iambus; the law of regressive accent dissimilation